Mercy street [videorecording (DVD)] - Grant, Shalita; Winstead, Mary Elizabeth (PBS Distribution, 2016)
It takes viewers beyond the battlefield and into the lives of Americans on the Civil War home front as they face challenges of one of the most turbulent times in our nation's history. This series is about the drama and unexpected humor of everyday life behind the front lines. It's a fresh twist on an iconic story, one that resonates with larger themes we still struggle with today.